Design, synthesis and activity evaluation of prodrug form JBP485 and Vitamin E for alleviation of NASH. (15th January 2022) - Wu, Bin; Zheng, Xu; Li, Xing; Wang, Changyuan; Li, Lei; Tang, Zeyao; Cui, Hongxia; Li, Zhen; Chen, Lixue; Ma, Xiaodong
Graphical abstract: Abstract: Non-alcoholic steatohepatitis (NASH) is a serious form of non-alcoholic fatty liver disease (NAFLD) characterized by liver steatosis with lobular inflammation, hepatocyte injury and pericellular fibrosis. JBP485 is a hydrophilic dipeptide with protective effects on liver through alleviation of oxidative stress and inhibition of hepatocyte apoptosis and ICAM-1 expression. Vitamin E (VE), as a powerful biological antioxidant, exerts a certain protective effect on cell membranes and lipoproteins from lipid peroxidation. In this study, on the basis of the structural characteristics of two agents, the prodrug form target of JBP485 and VE (JBP485-VE) was designed and synthesized via succinic acid linker. The synthesized compound significantly reduced the degree of inflammation and fibrosis according to hematoxylin-eosin (H&E) and sirius red staining assay for the liver tissue in CCl4 -induced NASH mouse model. The clear reduction of TG, T -CHO and ALT, AST content also demonstrated its efficacy in the treatment of NASH. In addition, JBP485-VE also reduced the expression of the inflammatory markers IL-2, IL-17A and malondialdehyde (MDA) in liver tissue, which indicated its higher anti-inflammatory and anti-oxidative stress activity. All these evaluated biological properties suggest that the strategy of prodrug design provided an effective method for the treatment of NASH.